Sabah from the Ground : The 2020 Elections and the Politics of Survival - Welsh, Bridget; Somiah, Vilashini; Loh, Benjamin YH (Strategic Information and Research Development Centre, 2021)
Sabah’s 2020 election was Malaysia’s first pandemic election. While attention centres on the election’s impact on the spread of Covid-19, this collection brings together scholars, journalists and social activists who were on the ground in Sabah to analyse what happened, why and the broader implications of the outcome for Sabah and Malaysian politics. The book is the first in-depth study of a Sabah election. It is also multidisciplinary – with authors from different perspectives and the majority of authors from Sabah. Traditional explanations prioritise the role of the federal-state relationship in shaping Sabah politics. Sabah from the Ground challenges this paradigm, suggesting that politics in Sabah needs to be better understood as a reflection of conditions within Sabah – as Sabahans struggle to navigate and survive on Malaysia’s periphery.